Predicting Hospital Readmissions from Home Healthcare in Medicare Beneficiaries. Issue 12 (29th August 2019) - Jones, Christine D.; Falvey, Jason; Hess, Edward; Levy, Cari R.; Nuccio, Eugene; Barón, Anna E.; Masoudi, Frederick A.; Stevens‐Lapsley, Jennifer
Abstract : OBJECTIVE: To use patient‐level clinical variables to develop and validate a parsimonious model to predict hospital readmissions from home healthcare (HHC) in Medicare fee‐for‐service beneficiaries. DESIGN: Retrospective analysis using multivariable logistic regression and gradient boosting machine (GBM) learning to develop and validate a predictive model. SETTING/PARTICIPANTS/MEAUREMENTS: A 5% national sample of patients, aged 65 years or older, with Medicare fee‐for‐service who received skilled HHC services within 5 days of hospital discharge in 2012 (n = 43 407). Multiple data sets were merged, including Medicare Outcome and Assessment Information Set, Home Health Claims, Medicare Provider Analysis and Review, and Master Beneficiary Summary Files, to extract patient‐level variables from the first HHC visit after discharge and measure 30‐day readmission outcomes. RESULTS: Among 43 407 patients with inpatient hospitalizations followed by HHC, 14.7% were readmitted within 30 days. Of the 53 candidate variables, seven remained in the final model as individually predictive of outcome: Elixhauser comorbidity index, index hospital length of stay, urinary catheter presence, patient status (ie, fragile health with high risk of complications or serious progressive condition), two or more hospitalizations in prior year, pressure injury risk or presence, and surgical wound presence. Of interest, surgical wounds, either from a total hip or total knee arthroplasty procedure or another surgical procedure, were associated with fewer readmissions. The optimism‐corrected c‐statistics for the full model and parsimonious model were 0.67 and 0.66, respectively, indicating fair discrimination. The Brier score for both models was 0.120, indicating good calibration. The GBM model identified similar predictive variables. CONCLUSION: Variables available to HHC clinicians at the first postdischarge HHC visit can predict readmission risk and inform care plans in HHC. Future analyses incorporating measures of social determinants of health, such as housing instability or social support, have the potential to enhance prediction of this outcome. J Am Geriatr Soc 67:2505–2510, 2019